The Dynamics of the Performance–Risk Relationship Within a Performance Period: The Moderating Role of Deadline Proximity - Lehman, David W.; Hahn, Jungpil; Ramanujam, Rangaraj; Alge, Bradley J. (Organization Science, 2011)
Risky organizational decisions are frequently made within the confines of performance periods with predefined durations and deadlines for achieving desired levels of performance. The relationship between performance and risk taking has been studied mostly across such periods but rarely within them. Building on the shifting-focus-of-attention model of organizational risk taking, we argue that the temporal proximity of deadlines regulates the focus of organizational attention within a performance period. Decision makers will focus their attention on attaining and maintaining aspirations early in a period; however, as deadlines approach, decision makers in underperforming firms will increasingly be likely to focus on ensuring survival, whereas decision makers in outperforming firms will increasingly be likely to focus on experimenting with slack resources. We propose that the relationship between performance and risk taking should thus be moderated by deadline proximity within a performance period. We tested and found support for our hypotheses in the context of 22,603 fourth-down decisions made by the 32 National Football League teams during the 2000–2005 regular season games. Our findings suggest that the notion of temporally bound performance periods and deadline proximity should play a more central role in attention-based frameworks of organizational risk taking.